Structure Elucidation of Lithium Compounds Using 7Li Residual Quadrupolar Couplings. Issue 23 (22nd March 2023) - Rüttger, Franziska; Patten, Tim; Kretsch, Johannes; Krawczuk, Anna; Stalke, Dietmar; John, Michael
Abstract: A new NMR method for the structure elucidation of lithium compounds under solution‐like conditions is presented. It is based on the measurement of 7 Li residual quadrupolar couplings (RQCs) in a stretched polystyrene (PS) gel, and comparison to RQCs predicted from crystal or DFT‐derived model structures in combination with alignment tensors derived from one‐bond 1 H, 13 C residual dipolar couplings (RDCs). The method was applied to five lithium model complexes containing monoanionic, bidentate bis(benzoxazole‐2‐yl)methanide, bis(benzothiazole‐2‐yl)methanide and bis(pyridyl)methanide ligands, of which two are first introduced in this work. In agreement with the crystalline state, four complexes are monomeric with Li coordinated fourfold by two additional THF molecules, whereas in one complex bulky t Bu groups only provide space for one additional THF molecule. Abstract : Getting to the solution : 7 Li residual quadrupolar couplings (RQCs) – obtained under weakly oriented conditions – provide a valuable piece of information about (organo‐)lithium association and solvation. In this work, the THF solvation of a range of lithium compounds was determined by comparing experimental RQCs to that calculated from 7 Li electric field gradients and molecular alignment.